1985
DOI: 10.1007/bf00283145
|View full text |Cite
|
Sign up to set email alerts
|

Experimental diabetes mellitus inhibits prostacyclin synthesis by the rat penis: pathological implications

Abstract: Summary. In view of the marked increase in blood flow into the penis during erection and the association of diabetes mellitus with impotence, we used the diabetic rat model to investigate the possibility that: (a) the penis may produce prostacydin; and (b) prostacyclin secretion may be decreased in diabetes. Rats given a high dose of streptozotocin (120 mg/kg body weight) developed acute ketotic diabetes and were killed after 48 h. Animals given a low dose of streptozotocin (65 rag/ kg body weight) developed n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 19 publications
1
24
0
Order By: Relevance
“…185,186 It was demonstrated some time ago that the formation of PGI 2 in cavernosal tissue is reduced in conditions that predispose to ED. [187][188][189][190][191] The administration of PGI 2 analogues, such as iloprost, have long been known to elicit vasculoprotective effects. 192 The administration of the PGI 2 analogue, beraprost, prevented the development of severe neuropathy in diabetic rats.…”
Section: Ros and Eicosanoidsmentioning
confidence: 99%
“…185,186 It was demonstrated some time ago that the formation of PGI 2 in cavernosal tissue is reduced in conditions that predispose to ED. [187][188][189][190][191] The administration of PGI 2 analogues, such as iloprost, have long been known to elicit vasculoprotective effects. 192 The administration of the PGI 2 analogue, beraprost, prevented the development of severe neuropathy in diabetic rats.…”
Section: Ros and Eicosanoidsmentioning
confidence: 99%
“…Organ bath experimentation involving the application of various putative eNOS agonists to isolated erectile tissue provides a basic strategy to investigate this issue, although the approach has generally relied on mechanical removal of endothelium and then inference as to how the tissue relaxation effects are altered in its absence. Problems inherent in this approach are the inconsistency of endothelium removal and, more importantly, the inability to discern whether the altered physiology is due to eNOS absence or absence of other possibly active vasodilators such as prostacyclin (Jeremy et al, 1985) released from the endothelium. The application of NOS inhibitors to assess eNOS biology is also deemed problematic because of nonselective inhibitory effects on other NOS isoforms such as nNOS.…”
mentioning
confidence: 99%
“…This finding should be considered in the light of pre vious studies which suggested that a relatively short peri od of diabetes causes alterations in the physiological mechanisms that modulate corpus cavemosal smooth muscle relaxation [3][4][5], an essential step for penile erec tion.…”
Section: Discussionmentioning
confidence: 99%
“…We also identified changes brought about by the onset of diabetes mellitus (DM), a common cause of erec tile dysfunction in both the rat model [5] and man [1], bitone (Sagatal; May and Baker, Dagenham, UK). Their penile tis sues were excised and stored immediately at -70° C in airtight cryotubes.…”
mentioning
confidence: 99%
See 1 more Smart Citation